2018
DOI: 10.1055/s-0038-1669418
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Management of Trigeminal Schwannoma: Cohort Analysis and Systematic Review

Abstract: Background Trigeminal schwannomas are benign tumors with a predilection for women between 40 and 60 years of age and account for less than 0.5% of all intracranial tumors. Clinical presentation depends on size and location, and typical symptoms are ipsilateral hypesthesia, headache, and facial pain. Clinical features and imaging usually make the Diagnosis. Methods A retrospective cohort analysis of 14 patients treated at our institution between January 1999 and October 2016 was performed, with a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…However, complete tumor resection could be associated with a variety of complications including meningitis, fistula formation, trigeminal neuralgia, and masseter muscle atrophy. [ 9 , 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, complete tumor resection could be associated with a variety of complications including meningitis, fistula formation, trigeminal neuralgia, and masseter muscle atrophy. [ 9 , 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…[3,13,14] In this case, we chose the retrosigmoid sub-occipital approach and the supprot from Modus V system, which can offer a good visual of the whole CPA and increase safety during tumor dissection from brainstem and lower cranial nerves. According to Li et al, [11] reported on 43 cases with trigeminal schwannoma received conventional surgical treatment, the postoperative rate of facial numbness remain at 82.8% of patients, other publications also reported similar data with associated morbidity was high at around 57% to 85% [4–10] (Table 1). Mainly due to only partial removal of the tumor, and TS arise from trigeminal nerve fiber which is hard to be recognized and protected during the operation.…”
Section: Discussionmentioning
confidence: 85%
“…With the tumor that have a maximal diameter of 4.8 cm, thus the stereotactic radiosurgery is not recommended, [2] and the surgery approach was chosen, with the ultimate goal is not only a removal of the big tumor at CPA but also functional preservation of all cranial nerves and recovery of quality of life. [1,10,11] The strengths of exoscopes are the wide view and deep focus with good illumination that can reduce the need for repositioning and refocusing during the surgery, hence better visual which is critical for surgery. Published data on the VITOM-3D, ORBEYE, and Modus V exoscope systems reported comparable results with the conventional surgical microscope with better image quality and illumination in surgeries.…”
Section: Authormentioning
confidence: 99%
“…1 Occurrence may be sporadic or in association with neurofibromatosis type 2, and malignant transformation is very rare. 2,3 Treatment entails surgical resection 4,5 or, increasingly, stereotactic radiosurgery. 6 Despite radiosurgery, approximately one-third of cases may progress and symptomatic improvement is seen in fewer than 50% owing to the challenging tumor location.…”
Section: Discussionmentioning
confidence: 99%